Die tertiären Ebenheiten des Haarstranges im Lichte neuerer geologisch-paläantologischer Forschungen - Hempel, Ludwig (ERDKUNDE, 1977)
Published in1962 the mapping of the tertiary peneplains of Haarstrang and its tectonically caused altitudes are supported by geologic-stratigraphical and sedimentological experiments. In addition a re-evaluation of the findings regarding the dependence/independence of the surface forms on the bedrock is presented.